Use of Immature Platelet Fraction as a Prognostic Marker in Dengue Fever - Hussain, Amina; Niaz, Asif; Younas, Muhammad Tahir; Qayyum, Uzma; Siddiqui, Fuad Ahmed; Uruj, Sana (Pakistan Armed Forces Medical Journal, 2024)
Objective: To investigate the relationship between immature platelet fraction and poor short-term prognosis in dengue fever patients.Study Design: Comparative cross-sectional study.Place and Duration of Study: Pakistan Air Force Hospital, Islamabad Pakistan, from Oct to Dec 2022.Methodology: In this study, a total of 300 cases had a confirmed diagnosis of dengue fever and were admitted to the hospital. An immature platelet fraction was performed on all the patients on the fifth day of febrile illness. All the patients were monitored closely by the treating team at 24, 48, and 72 hours for the presence of thrombocytopenia on the complete blood picture or other clinical complications of dengue fever.Results: In the study, the median age of patients with dengue fever was 36(IQR-42) years. Out of 350 patients, 239(68.2%) were males, while 111(31.8%) were females. 282(80.5%) patients had a good prognosis, while 68(19.5%) did not have a good prognosis and showed clinical or haematological manifestations. On the fifth day of illness, 279(79.7%) had an IPF of >10%, whereas 71(20.3%) had an IPF of